Rotation and orientation of irregular particles in viscous fluids using the gradient smoothed method (GSM). Issue 1 (1st January 2017) - Shao, Bing; Liu, G. R.; Lin, Tao; Xu, George X.; Yan, Xiangzhen
ABSTRACT: The dynamics (rotation and stabilization) of single irregular particles that are constrained to rotate only and until to a quasi-steady state in a two-dimensional channel with viscous flow is numerically investigated using the gradient smoothed method (GSM). The GSM is proved to be computationally stable for arbitrary, irregular geometries discretized with distorted grids and well agreements with others' work are revealed in validation cases. This work focuses on the influences of irregular particles' typical shapes, including ellipse, rectangle and triangle, on the relevant surface forces, the flow dynamics, and the response time of the rotation. The effects of aspect ratio and flow velocity are studied in detail for all three typical types of irregular particles. It is found that the imbalance of the total torque on the surface of the particle causes the rotation, and when the particle is approaching the final stable position, the total torque becomes nearly zero with a small fluctuation, which contributes a local oscillation around the stable direction. In our cases, under the constraints, it is found also that the broad side of the elliptical particle always tends to be along the stream. For the rectangular particle, however, the aspect ratio and the flow velocity collectively determine the final orientation which means the major side or the diagonal line is along the flow stream. In addition, the triangular particle is found to behave quite differently in terms of both rotation and stabilization. The 'response time' of three types of particles is finally obtained from our GSM simulations. These findings could be helpful for a better understanding on the fluid-particle interactions and maybe advisory for determining the shape factor which is a key parameter for multiple particles motions.